We Need to Talk About Quality of Life with Cancer Patients: Primum Non Nocere in Oncology - Vlad Bogin (Medicina)
The Hippocratic principle primum non nocere, or “first, do no harm”, serves as a vital lens through which to re-evaluate modern oncology practices. While recent advances such as immunotherapy, targeted agents, and precision medicine have transformed cancer care, these treatments are not without risk. Even with improved tolerability, they may still lead to substantial toxicities, particularly in frail patients with advanced cancer. The pursuit of survival often overshadows the patient’s quality of life, with aggressive interventions frequently continuing beyond the point of meaningful benefit. This perspective article argues for a more individualized and ethically grounded approach to cancer treatment, emphasizing the careful assessment of each patient’s clinical status, values, and goals. By integrating geriatric and palliative assessments, improving shared decision making, and moving away from a default treatment-at-all-costs mindset, clinicians can better align care with what truly matters to patients. Honoring primum non nocere in oncology means not only extending life when appropriate but ensuring that life remains worth living.